Of bars and stripes: A Malawi cichlid hybrid cross provides insights into genetic modularity and evolution of modifier loci underlying colour pattern diversification. Issue 19 (7th August 2021) - Gerwin, Jan; Urban, Sabine; Meyer, Axel; Kratochwil, Claudius F.
Abstract: Understanding the origins of phenotypic diversity among closely related species remains an important largely unsolved question in evolutionary biology. With over 800 species, Lake Malawi haplochromine cichlid fishes are a prominent example of extremely fast evolution of diversity including variation in colouration. Previously, a single major effect gene, agrp2 ( asip2b ), has been linked to evolutionary losses and gains of horizontal stripe patterns in cichlids, but it remains unknown what causes more fine‐scale variation in the number and continuity of the stripes. Also, the genetic basis of the most common colour pattern in African cichlids, vertical bars, and potential interactions between the two colour patterns remain unknown. Based on a hybrid cross of the horizontally striped Lake Malawi cichlid Pseudotropheus cyaneorhabdos and the vertically barred species Chindongo demasoni we investigated the genetic basis of both colour patterns. The distribution of phenotypes in the F2 generation of the cross indicates that horizontal stripes and vertical bars are independently inherited patterns that are caused by two sets of genetic modules. While horizontal stripes are largely controlled by few major effect loci, vertical bars are a highly polygenic trait. Horizontal stripes show substantial variation in the F2 generation that, interestingly, resemble naturally occurring phenotypes found in other Lake Malawi cichlid species. Quantitative trait loci (QTL) mapping of this cross reveals known ( agrp2 ) and unknown loci underlying horizontal stripe patterns. These findings provide novel insights into the incremental fine‐tuning of an adaptive trait that diversified through the evolution of additional modifier loci.